2012
DOI: 10.1371/journal.pone.0049531
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and Carbon Isotope Variations in a Modern Rodent Community – Implications for Palaeoenvironmental Reconstructions

Abstract: BackgroundThe oxygen (δ18O) and carbon (δ13C) isotope compositions of bioapatite from skeletal remains of fossil mammals are well-established proxies for the reconstruction of palaeoenvironmental and palaeoclimatic conditions. Stable isotope studies of modern analogues are an important prerequisite for such reconstructions from fossil mammal remains. While numerous studies have investigated modern large- and medium-sized mammals, comparable studies are rare for small mammals. Due to their high abundance in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 99 publications
0
32
0
Order By: Relevance
“…Thus, the oxygen isotopic composition in mammalian tooth is influenced by the atmospheric O 2 , and water directly drunken from natural water bodies or present in their food, but only the latter two are highly variable and capable to explain the differences among taxa (Sponheimer and LeeeThorp, 2001 (Kohn et al, 1996;Helliker and Ehleringer, 2000). Nevertheless, some studies show that the d 18 O values of tooth apatite is a reflection of the isotopic composition of the meteoric and environmental water which megamammals were drinking, because large mammals (those with an obligatory drinking behavior) obtain most of the water by drinking rather than from their diets (Bryant and Froelich, 1995;Gehler et al, 2012). In the late Pleistocene of Southern Brazil, Lopes et al (2013) found a poor correlation between the d 18 O and d 13 C values for fossils of N.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the oxygen isotopic composition in mammalian tooth is influenced by the atmospheric O 2 , and water directly drunken from natural water bodies or present in their food, but only the latter two are highly variable and capable to explain the differences among taxa (Sponheimer and LeeeThorp, 2001 (Kohn et al, 1996;Helliker and Ehleringer, 2000). Nevertheless, some studies show that the d 18 O values of tooth apatite is a reflection of the isotopic composition of the meteoric and environmental water which megamammals were drinking, because large mammals (those with an obligatory drinking behavior) obtain most of the water by drinking rather than from their diets (Bryant and Froelich, 1995;Gehler et al, 2012). In the late Pleistocene of Southern Brazil, Lopes et al (2013) found a poor correlation between the d 18 O and d 13 C values for fossils of N.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the results of several studies indicated that bioapatite δ 18 O carb values in enamel are higher than those of bone, whereas neither the enamel nor the bone δ 18 O phos values were consistently higher. Webb et al suggested that different fractionations of blood bicarbonate during bioapatite formation and maturation cause 18 O‐(and 13 C‐)enriched structural carbonate in enamel versus bone apatite, and Gehler et al explained this gap by different time intervals in the mineralization of the two tissues. Nevertheless, because the structure of dentine is more similar to that of bone than to enamel, we also expect lower δ 18 O carb values in dentine than in enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Yet micromammals are common in the fossil record and make up an important component of terrestrial ecosystems, and with their generally high fecundities, high local densities, and population growth rates, they hold tremendous potential as sensitive and quickly responding recorders of environmental changes. Other than size-imposed restrictions, micromammalian isotopic proxy records show no disadvantage compared to larger animals (Gehler et al, 2012) and have proven useful in a number of pioneering studies (e.g. Grimes et al, 2005;Hopley et al, 2006;Yeakel et al, 2007;Hynek et al, 2012;Kimura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%